Soil Water Interaction under Different Tree Plantations - Jha, M. N.; Gupta, M. K.; Pandey, Rajiv (Indian Forester, 2009)
A study on soil water retention pattern under Chir (Pinus roxburghii), Khair (Acacia catechu), Eucalyptus (Eucalyptus hybrid) plantation and barren land was conducted in Mussoorie Forest Division (UK). Multivariate test showed that the mean soil retention changes across the different soil depth. The maximum amount of water was retained by the soils under Khair (356.90 to 879.40 k lit/ha) followed by Chir (286.73 to 913.13 k lit/ha), Eucalyptus (212.50 to 932.50 k lit/ha) and the least under barren land (116.27 to 824.03 k lit/ ha) during the different months of the year. Good amount of water can be retained by the soils under plantation even in the drier months of April (255.20 to 393.27 k lit/ha) to June (21.50 to 356.90 k lit/ha) as compared to barren land (116.27 to 221.0 k lit/ha). Even in the driest month of May, surface layer can hold 148.89 % and over all entire profile by 217.73 % more water under plantations as compared to barren land. In drier months, lower layers had higher retention as compared to upper layers. From July to September, soil profile retained maximum water because entire profile gets recharged due to rainfall.